Distribution of outage intervals in macrodiversity cellular systems. - Graziosi, F. (IEEE Journal on selected areas in communications)
A general model for the analysis of outage intervals in mobile radio systems with macrodiversity is proposed. In a log-normal shadowing environment, reception diversity from two base stations is considered in the general case of different fading margins. Through a level-crossing analysis, the probability density function (PDF) of the outage interval is derived. It is seen that exact expressions can be obtained for the average outage occurrence rate and the average outage duration. The exact expressions are used to also improve the accuracy of the PDF at small values of the fading margins, by forcing the PDF to meet the exact average through a proper choice of its parameters. As a particular case, explicit solutions are derived for minimum duration outages